Sistem Pendukung Keputusan dalam Penentuan Pemberian Pinjaman Uang Pada Anggota Swasti Sari dengan Metode Promethee (Yayasan Kawanad, 2023)
Credit Cooperative (KOPDIT) Swasti Sari is a financial institution founded in 1988 in East Nusa Tenggara. Every year, these cooperative experiences a significant development, seen from the increase in assets and the number of members who continue to grow. Determination of credit policies by cooperatives requires the formulation of standard and credit requirements that include customer character, credit payment capacity, capital capability, and guaranteed customers. Provision of appropriate credit is very important and requires effective and efficient service. However, credit administration procedures in this cooperative are still not effective and often the granting of credit is not on target. This study aims to assist cooperative managers in making decisions on loan or credit to members using the Promethee method. This method is an auto ranking method that helps decision makers analyze multicriteria problems and determine the priority of receiving loan application. The results of the study are expected to be a reference in the development of a decision support system for the determination of loans in the Swasti Sari Cooperative.